Methods and techniquesA new strategy to identify potentially dangerous coronary arterial patterns before percutaneous pulmonary valve implantation - Góreczny, Sebastian; Eicken, Andreas; Ewert, Peter; Morgan, Gareth John; Fratz, Sohrab (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Despite advances in surgical techniques, right ventricular outflow tract (RVOT) conduits are prone to fail over time. Percutaneous pulmonary valve implantation was introduced to expand the lifetime of these conduits and to decrease the number of open heart operations during a patient’s lifetime. The procedure can be performed with excellent results; however, serious complications such as coronary arterial compression and conduit rupture have been reported. We present percutaneous treatment of a patient after Ross-Konno operation with RVOT conduit dysfunction and a potentially problematic course of the left anterior descending artery.